Online shared GIS saves resources. - Rader, Jason (American City & County, 2000)
Rather than going to the expense of implementing a local GIS system, some local governments are using existing resources to access a GIS that is published over the Internet. Published geospatial information available via specialized software allows anyone with an Internet connection and a PC to avail of a complex GIS. This enables smaller and less populated counties to take part in complex geospatial analysis without footing the bill for a specific local application.